Challenges to using evidence from systematic reviews to stop ineffective practice: an interview study. (July 2013) - Shepperd, Sasha; Adams, Richard; Hill, Alison; Garner, Sarah; Dopson, Sue
Objectives: To examine the challenges to using systematic review evidence to develop guidance for decommissioning ineffective health services, and the problems experienced by clinicians and commissioners when they attempt to implement the evidence from this guidance. Methods: Interviews with 23 clinicians and 15 commissioners from nine commissioning organizations (Primary Care Trusts) in the south of England. Results: Participants identified generic and intervention-specific barriers to using systematic review evidence to develop and implement decommissioning. Generic barriers included: contradictions within the health care system arising from policy; managing a high volume of evidence; difficulty in applying the evidence to the local context; and patient or parent expectations. Intervention-specific factors included: the influence of industry; an absence of systems for monitoring local implementation of guidance; and the availability of different codes for the same procedure which made monitoring some practices unreliable. Conclusions: The micro practices of commissioners are shaped by the wider system of health policy, the knowledge producing and delivery agencies associated with health care, and power dynamics within the health care system. If decommissioning is to be guided by evidence, then adequate resources to support the process are necessary. This includes long-term engagement of clinicians, providing alternatives to the decommissioned activity and tackling perverse incentives. An important precursor to decommissioning is obtaining data on the nature and extent of current clinical practice and using these data to monitor variation in the implementation of guidance.